KONDISI SUMBER DAYA MANUSIA PADA USAHA PERHOTELAN DI KOTA DILI, TIMOR-LESTE - Riberio, Finia; Alam Paturusi, Syamsul; Oka Prasiasa, Dewa Putu (JURNAL MASTER PARIWISATA; Volume 04, Nomor 02, Januari 2018, 2018)
This article is a research about the development of human resources in the hotel business in Dili, Timor Leste. This area has higher total number of employees compare to other areas in Timor-Leste though the foreign labour force still dominates in the management level and professional specialist, although number of local employee is bigger than number of foreign employee. The aim of this article is to nd out the condition of human resources and managerial e orts regarding to development of employees in the hotel business in Dili. The data collection is through deep interviews, eld observation and documentation study such as purposive sampling. The result of research shows that currently hotel employees trully need coaching and instruction in improving employees’ performances. Other than that, the mangerial part of the hotel business maintain their cooperation with the related government and educational institutions in providing opportunities for the hotel employees to participate in training and education in the hospitality field.